2013
DOI: 10.1111/ele.12091
|View full text |Cite
|
Sign up to set email alerts
|

Conserving large carnivores: dollars and fence

Abstract: Conservationists often advocate for landscape approaches to wildlife management while others argue for physical separation between protected species and human communities, but direct empirical comparisons of these alternatives are scarce. We relate African lion population densities and population trends to contrasting management practices across 42 sites in 11 countries. Lion populations in fenced reserves are significantly closer to their estimated carrying capacities than unfenced populations. Whereas fenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
241
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(248 citation statements)
references
References 42 publications
5
241
1
1
Order By: Relevance
“…2013) and might also be causal to the limited risk effects observed. Indeed, where direct lion associated risk effects have been detected, lion densities have generally been much higher than the 2.1 lions/100 km 2 in our study site [Thaker et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…2013) and might also be causal to the limited risk effects observed. Indeed, where direct lion associated risk effects have been detected, lion densities have generally been much higher than the 2.1 lions/100 km 2 in our study site [Thaker et al.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, predators, including lions, occur at naturally or artificially low densities in several ecosystems already (Packer et al. 2013; Bauer et al. 2015), and studies need to incorporate such areas before general conclusions about risk effects can be reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our Masai Mara analysis was based on the best available data for the reserve as a whole: A 12-mo study in 1991-1992 and Dloniak's 2005 survey, cited by Packer et al (2), that replicated the earlier methods and indicated a 40% decline in 14 years. Kiffner et al's 2005 survey in Katavi (3) responded to conservation concerns over declining ecosystem health (4) and reported a lion density of only 15% of estimated carrying capacity (168 lions compared with an expected 1,100) (2).…”
mentioning
confidence: 99%
“…Packer et al, 2010). While some are advocating radical new measures for protection such as fencing (Packer et al, 2013) and lifting the rhino horn trade ban (Biggs et al, 2013), we do not yet know whether they will be implemented nor how effective they will be. How soon before the Big 5 becomes the Big 4 or the Big 3?…”
mentioning
confidence: 99%